Evaluasi Tata Kelola Keamanan Informasi Pada Dinas Komunikasi Dan Informatika Kota Malang Menggunakan Indeks KAMI - Marinda Yunella; Admaja Dwi Herlambang; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The information technology was emphasized on concept of information share which aimed to support public service. This information was referred as valuable asset which needed to the government protection through the management of information security. Currently, the management of information security in Dinas Komunikasi dan Informatika (KOMINFO) Kota Malang has not been optimally implemented. This condition due to some technical problems related to information security issue which have been occurred repeatedly. On the evaluation of Electronic-Based Government System in 2018, KOMINFO has achieved less maximal result. The security was an important aspect in this valuation. Besides, the institution did not have certification on information security management system which was required by the Central Government. Therefore, this research aimed to evaluate the information security by means of KAMI index 4.0 version. Based on the evaluation, the result was exerted as a basic of improvement recommendation which functioned to support the process of information security improvement in appropriate to standard equipment SNI/ISO 27001:2013. Further, according to this evaluation result, it showed the Level of Completeness 246 and maturity level on level I+. Thus, from this last evaluation result, KOMINFO was categorized as not feasible to the completeness of standard implementation SNI/ISO 27001:2013. As the consequence, it resulted to 9 recommendations on governance area, 13 recommendation on risk management area, 12 recommendation on framework area, 16 recommendations on asset management area, 9 recommendations on technology and security area, and 9 recommendations on supplementary area which were proposed to complete the equipment of information security implementation.